Composition of Pacepuk Sang Hyang | Karya Musik Pacepuk Sang Hyang - I Made Dwi Andika (GHURNITA: Jurnal Seni Karawitan, 2021)
Composition Pacepuk Sang Hyang is a composition which is born from the response toward the combination between the spirit of gending with the character of Sang Hyang Dedari, Sang Hyang Jaran, and Sang Hyang Bojog. The interest of the creator to use the three types of gending Sang Hyang as the sources of creation are located at 1) the uniquenes of direction of tones in forming melody patterns, 2) concept of ngubeng is one of attraction of gending Sang Hyang’s melody, 3) the barrel of tones used in the gending Sang Hyang tend to be slendro. The essence of three gending and characters of Sang Hyang are treated become a new composition because the characteristic features of Pacepuk Sang Hyang are based on the creativities of intellectuality and tend to be music for music. Structurally, composition Pacepuk Sang Hyang is divided into three parts of creation. The first part, the creator was inspired from Sang Hyang Bojog. The second part, the creator was inspired from Sang Hyang Jaran. The third part, the creator was inspired from Sang Hyang Dedari. The purposes of usic composition Pacepuk Sang Hyang is to rise the sources of creation in form of Sang Hyang arts as a local wisdom which is getting dim by reproducing in different packages using creativities. The realization step is located in creativity process which contains assessment step, trial step, and formation step.